Inconsistent shock advisories for monomorphic VT and Torsade de Pointes – A prospective experimental study on AEDs and defibrillators. (July 2015) - Fitzgerald, Abi; Johnson, Meshell; Hirsch, Jan; Rich, Mary-Ann; Fidler, Richard
Abstract: Background: Cardiovascular disease and sudden cardiac arrest are the leading causes of death in the United States. Early defibrillation is key to successful resuscitation for patients who experience shockable rhythms during a cardiac arrest. It is therefore vital that the shock advisory of AEDs (automated external defibrillators) or defibrillators in AED mode be reliable and appropriate. The goal of this study was to better understand the performance of multiple lay-rescuer and hospital professional defibrillators in AED mode in their analysis of ventricular arrhythmias. The measurable objectives of this study sought to quantify: 1. No shock advisory for sinus rhythms at any rate. 2. Recognition and shock advisory for ventricular fibrillation (VF). 3. Recognition and shock advisory for monomorphic ventricular tachycardia (VT). 4. Recognition and shock advisory for Torsades de Pointes (TdP). Methods: This is a prospective evaluation of two AEDs and four semi-automatic, hospital professional defibrillators. This study represents post-marketing evaluation of FDA approved devices. Each defibrillator was connected to multiple rhythm simulators and presented with simulated ECG waveforms 20 consecutive times at various rates when possible. Results: All four defibrillators and both AEDs tested consistently recognized normal sinus rhythm (NSR) from all rhythm sources, and did not recommend a shock for NSR at any rate (from 80 to 220 bpm). All four defibrillators and both AEDs recognized VF from all rhythm sources tested and recommended a shock 100% of the time. Variations were found in the shock advisory rates among defibrillators when testing simulated VT heart rates at or below 150 bpm. One AED tested did not consistently advise a shock for monomorphic VT or TdP at any tested rate. Conclusion: Lay-rescuer AEDs and professional hospital defibrillators tested in AED mode did not reliably recommend a shock for sustained monomorphic VT or TdP at certain rates, despite the fact that it is a critical component of the currently recommended treatment. These findings require further examination of the risk benefit analysis of shocking or not shocking rhythms such as TdP or pulseless VT.